Clinical outcomes of serum potassium in patients with percutaneous coronary intervention: insights from a large single-center registry - Ke, Bingbing; Shen, Aidong; Qiu, Hui; Li, Weiping; Chen, Hui; Li, Hongwei (Frontiers in Cardiovascular Medicine, 2023)
Background Serum potassium homeostasis plays an important role in myocardial electrical stability, but the impact of altered serum potassium levels on the major adverse cardiovascular and cerebral events (MACCE) in patients with percutaneous coronary intervention (PCI) has not been evaluated. Aim To evaluate the association between serum potassium level and the risk of MACCE in PCI patients. Materials and methods This retrospective study involved 8,263 in-patients from a single-center registry who were successfully treated with PCI between January 2003 and December 2020. Clinical data were collected for 24 h after admission. Data were analyzed from June 2003 to December 2021. The primary outcome was MACCE, defined as a composite of all-cause death, myocardial infarction, revascularization, stroke, and heart failure-related hospitalization. Results The median [interquartile range (IQR)] follow-up for all patients was 4.0 (2.1, 5.8) years, and 1,632 patients (19.7%) were diagnosed with MACCE. High serum potassium levels were associated with a 20% increased risk of MACCE (hazard ratio [HR]: 1.20, 95% confidence interval [CI]: 1.05–1.38, P = 0.008) and 72% increased risk of all-cause death (HR: 1.72, 95% CI: 1.39–2.14, P < 0.001). Multivariate Cox analysis showed that the risk of MACCE was higher in patients at the highest quartile of serum potassium (Q4 vs. Q1: adjusted HR: 1.18, 95% CI: 1.02–1.35, P = 0.026). Moreover, a higher serum potassium level was always associated with a higher risk of all-cause death (Q4 vs. Q1: adjusted HR: 1.50, 95% CI: 1.17–1.91, P = 0.001). A U-shaped relationship between serum potassium levels, MACCE, and all-cause death was derived in patients undergoing PCI. Serum potassium levels, maintained within the range of 3.8–4.0 mmol/L before PCI, exhibited the lowest risk of associated MACCE and all-cause death. Conclusion Our results demonstrate that the serum potassium level could be associated with higher risks of MACCE and all-cause death in PCI patients. In particular, serum potassium levels maintained at 3.8–4.0 mmol/L before PCI could lower the risk of MACCE and all-cause death.